Pemahaman Mahasiswa Tentang Efek Fotolistrik - Siswoyo Siswoyo (Universitas Negeri Jakarta, 2015)
Abstract This study describes the student's understanding of the photoelectric effect theoretically and empirically by using PhET Interactive Simulation. Survey techniques was conduct to obtain data on students' understanding of the photoelectric effect on students of Department of Physics, State UNJ class of 2012. Data were taken while students were following the lecture for 30 minutes, the number of respondents were 75 students. Research instrument consist of several questions related to the understanding of the photoelectric effect, such as, the definition of the photoelectric effect, the use of PhET Integrative Simulation on the topic of the photoelectric effect, the relationship between light intensity, frequency or wavelength, and the potential difference, analyzing, reading and drawing graphs relationship between the light intensity, frequency or wavelength and the potential difference. Data were analyzed qualitatively and quantitatively. The results showed that the students' understanding of the photoelectric effect is still low, especially when associated with the use of interactive simulations PhET. Keywords: Comprehension, Photoelectric Effect, PhET Interactive Simulation Abstrak Penelitian ini bertujuan untuk mendeskripsi pemahaman mahasiswa tentang efek fotolistrik dan mengkajinya secara teoritis maupun empiris dengan menggunakan PhET Interactive Simulation. Untuk memperoleh data tentang pemahaman mahasiswa tentang efek fotolistrik digunakan teknik survey pada mahasiswa Jurusan Fisika FMIPA UNJ angkatan 2012. Data diambil pada saat mahasiswa masing-masing angkatan sedang mengikuti perkuliahan dengan menggunakan waktu 30 menit, dengan jumlah responden sebanyak 75 mahasiswa. Intrumen penelitian berisi pertanyaan-pertanyaan yang terkait dengan pemahaman tentang efek fotolistrik, antara lain definisi efek fotolistrik, penggunaan Simulasi Interatif PhET pada topik efek fotolistrik, hubungan antara intensitas cahaya, frekuensi atau panjang gelombang, dan beda potensial, menganalisis, membaca dan menggambar grafik hubungan antara intensitas cahaya, frekuensi atau panjang gelombang dan beda potensial. Data dianalisis secara kualitatif dan kuantitatif sederhana. Hasil penelitian menunjukkan bahwa pemahaman mahasiswa tentang efek fotolistrik masih rendah, terutama bila dikaitkan dengan penggunaan simulasi interaktif PhET. Kata-kata kunci: Pemahaman, Efek Fotolistrik, PhET Interactive Simulation